Kontribusi Kitab Imamat Terhadap Kekudusan Gereja - Panggabean, Lenny Susi R. (KERUGMA: Jurnal Teologi dan Pendidikan Agama Kristen, 2023)
Abstract:  The aim of this research is to discover the benefits of the book of Leviticus, with the hope that the book of Leviticus can be seen as a book that should be appreciated and studied, not avoided because its content is full of boring sharia and symbols. In finding the benefits of the book of Leviticus, a qualitative method was used, using the book of Leviticus as the main source and a bibliographic approach. The results of the discussion in this research are: first, to explain the idea of the redemption of Jesus Christ, which can only be understood through the concept of sacrifices in the book of Leviticus. Without this system of sacrifices, it is very difficult to understand the concept of the atonement of Jesus Christ. Second, sanctifying the Sabbath days can be the basis for the church to sanctify Sundays as a day of rest and consecrate them to God for worship, prayer, and complete dependence on God's care. In the seventh year and the peak of the Sabbath, namely the jubilee year, the land is left uncultivated to maintain the preservation of nature, and to preserve life and protect God's people from greed, including exploitation of humans and nature, it is still relevant to serve as a basis for the church to share love, pay attention to the interest’s other people and the natural environment. Third, the concept of the holiness of the Israelites can be a guide for the holiness of the church today. Acts of incest, polygamy, infidelity, uncleanness are acts of the flesh that must be put to death in the lives of believers, because these acts violate God's holiness and bring God's wrath to His people. Keywords: Holiness; the book of Leviticus; believers.AbstrakAdapun tujuan dari penelitian ini adalah untuk menemukan manfaat kitab Imamat, dengan harapan kitab Imamat dapat dipandang sebagai kitab yang harus dihargai dan dipelajari bukan untuk dihindari karena isinya yang penuh dengan syariat dan lambang-lambang yang membosankan. Dalam menemukan manfaat kitab Imamat digunakan metode kualitatif, dengan menggunakan kitab Imamat sebagai sumber utama dan pendekatan kepustakaan. Adapun hasil dari pembahasan dalam penelitian ini adalah: pertama, untuk menjelaskan gagasan penebusan Yesus Kristus, hanya dapat dipahami melalui konsep korban-korban dalam kitab Imamat. Tanpa sistim korban-korban itu, sangat sulit memahami konsep penebusan Yesus Kristus. Kedua, pengudusan hari-hari sabat dapat menjadi dasar gereja  untuk menguduskan hari minggu sebagai hari perhentian untuk beristirahat dan menguduskannya bagi Tuhan untuk beribadah, berdoa, dan bergantung penuh kepada pemeliharaan Tuhan. Pada tahun  ketujuh dan puncak sabat yaitu tahun Yobel tanah dibiarkan tidak diolah untuk tetap menjaga kelestarian alam, dan untuk pemeliharaan kehidupan serta terhindarnya umat Tuhan dari sifat keserakahan, termasuk eksploitasi manusia dan alam, masih relevan dijadikan sebagai dasar bagi gereja untuk berbagi kasih, memperhatikan kepentingan orang lain dan alam sekitar. Ketiga, konsep kekudusan bangsa Israel dapat menjadi pedoman bagi kekudusan gereja masa kini. Perbuatan inses, poligami, perselingkuhan, kenajisan adalah perbuatan daging yang harus dimatikan dalam hidup orang percaya, karena perbuatan itu melanggar kekudusan Allah dan mendatangkan murka Allah kepada umat-Nya.